2022
DOI: 10.1021/acs.jmedchem.2c00589
|View full text |Cite
|
Sign up to set email alerts
|

Dual Targeting of Steroid Sulfatase and 17β-Hydroxysteroid Dehydrogenase Type 1 by a Novel Drug-Prodrug Approach: A Potential Therapeutic Option for the Treatment of Endometriosis

Abstract: A novel approach for the dual inhibition of steroid sulfatase (STS) and 17β-hydroxysteroid dehydrogenase type 1­(17β HSD1) by a single drug was explored, starting from in-house 17β HSD1 inhibitors via masking their phenolic OH group with a sulfamate ester. The sulfamates were intentionally designed as drugs for the inhibition of STS and, at the same time, prodrugs for 17β-HSD1 inhibition (“drug-prodrug approach”). The most promising sulfamates 13, 16, 18–20, 22–24, 36, and 37 showed nanomolar IC50 values for S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 117 publications
(186 reference statements)
0
3
0
Order By: Relevance
“…A designed multiple ligand approach using the merged pharmacophore strategy�that was previously reported 19 �was successfully applied. A newly developed metabolically stable 17β-HSD1 inhibitor class 20 (e.g., compound 3) was used to build the aryl sulfamate pharmacophore which is essential for STS inhibition. In the first step, the position of the sulfamate moiety on the benzoyl ring (ring B, see Figure 2) was aimed to be optimized, resulting in compounds 5 and 6, which were the first dual inhibitors of this class.…”
Section: ■ Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…A designed multiple ligand approach using the merged pharmacophore strategy�that was previously reported 19 �was successfully applied. A newly developed metabolically stable 17β-HSD1 inhibitor class 20 (e.g., compound 3) was used to build the aryl sulfamate pharmacophore which is essential for STS inhibition. In the first step, the position of the sulfamate moiety on the benzoyl ring (ring B, see Figure 2) was aimed to be optimized, resulting in compounds 5 and 6, which were the first dual inhibitors of this class.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…17 In a randomized phase I proof-of-principle clinical study, it was further found that STS inhibition has no effect on the levels of systemic E2. 18 In a recent work, our group introduced the idea of dual inhibition of both STS and 17β-HSD1 by designing multiple ligands 19 and via a drug−prodrug approach 20 as a novel treatment option for EDDs. Compound 1 (Table 1) had a promising profile, as it showed well-balanced intracellular activity against both target proteins, with IC 50 values of 15 and 22 nM for STS and 17β-HSD1, respectively, with an irreversible mode of action toward STS.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Therefore, the development of dual inhibitors targeting multiples steps in the intracrine network is a useful and promising approach. Effective molecules have been developed, like the dual aromatase-sulfatase inhibitor STX681 (Foster et al, 2008), and other inhibitors (Woo et al, 2010;Woo et al, 2011;Harrelson and Lee, 2016) and the sulfatase-HSD17B1 inhibitor (Mohamed et al, 2022). Also the approach of combining pre-receptor (or intracrine) drugs and receptor-blocking agents deserves attention in the future to obtain a complete shut down of the hormone signalling.…”
Section: Perspectivesmentioning
confidence: 99%